Issues On the Application of Critical Thinking Technology in English Lessons (Eurasian Journal of Learning and Academic Teaching, 2022)
The article deals with the issues based on the usage of critical thinking technology in English lessons. As we know, a person with critical thinking meets all the requirements of modern society. He/she knows how to see problems and prospects, set clear goals, develop optimal ways to achieve them. He/she has a clear, original, independent thinking, ready for self-realization and self-expression. Works on the development of critical thinking in the process of teaching English allows students to form socially significant, moral and value motives of behavior, increase the level of socialization, develop creativity and reflection, cultivate initiative, communication, dynamism - everything that is significant for the formation of needmotivational and operational -technical spheres of the student.